Disabilitas dan Hospitalitas: Rekonstruksi Teologi Hospitalitas dalam Lingkaran Pastoral - Susi Susi; Halim Wiryadinata (Jurnal Teologi Gracia Deo, 2023)
This study aims to show the reconstruction of the hospitality concept among disabilities in the light of the Pastoral Circle. The discrimination treatment for disabilities is the unbalanced of life among disabled people to exist in the community. Religion and psychology elements discover the limited approach through the infrastructures and the equipment for the disabilities. Religion is supposed to connect reality and the afterlife unable to work in the community. While the psychology element evaluates the acceptance of disabled people, they are rejected in the community. Through the pastoral circle method, this research analyses the four important points, which are insertion, social analysis, theological reflection, and pastoral planning to discover the redefintion of hospitality. The result is that the reconstruction of hospitality is the real action to fight along the ethical religious values without looking at their background. Finally, the conclusion is to impose the holistic program through infrastructure and equipment along the religious values to help them to exist in the community. AbstrakPenelitian ini bertujuan untuk merekonstruksi konsep hospitalitas diantara disabilitas dalam perspektif Lingkaran Pastoral. Faktor diskriminasi bagi disabilitas menciptakan ketidak-seimbangan di tengah masyarakat untuk mengakui keadaan mereka. Elemen agama dan psikologi menemukan ketidakberdayaan disabiltas melalui infrastruktur dan perlengkapannya. Agama yang diharapkan untuk menghubungkan antara realitas dan kehidupan yang akan datang belum mampu berperan didalam komunitas. Elemen psikologi mengevaluasi penerimaan disabiltas di masyarakat, tetapi mereka ditolak. Melalui metode lingkaran pastoral, studi ini memiliki empat poin utama yaitu permasalahan, sosial analisis, refleksi teologi, dan rencana pastoral untuk merekonstruksi konsep hospitalitas. Hasil dari penelitian ini bahwa redefinsi hospitalitas adalah tindakan nyata melalui nilai-nilai religi untuk memperjuangkan disabilitas di tengah masyarakat. Kesimpulannya yaitu menerapkan program hoslitik melalui infrastruktur and perlengkapannya untuk membantu mereka diterima di tengah masyarakat sesuai dengan nilai-nilai religi.